Et 3 N- Promoted Cascade Sp 3 C-H Bond Functionalization of Methyl Arene with Active Methylene CompoundsUnder Solvent-Free Condition - Kumar D.; Kumari S.; Gajaganti S.; Srivastava V.; Singh S. (My University, 2025)
We herein report the Et 3 N catalyzed sp 3 C−H bond functionalization of methyl arenes with active methylene compounds under solvent-free condition using TBHP as an oxidant. These reactions are exclusively enabled by TBHP. The methyl arenes used in this reaction are highly versatile and rapidly undergo oxidation and further condensation with malononitrile /ethylcyanoacetate. This is a metal-free, practical, inexpensive, non-toxic and environmentally benign method. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim